2016
DOI: 10.1124/dmd.115.069203
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disposition of Osimertinib in Rats, Dogs, and Humans: Insights into a Drug Designed to Bind Covalently to a Cysteine Residue of Epidermal Growth Factor Receptor

Abstract: Preclinical and clinical studies were conducted to determine the metabolism and pharmacokinetics of osimertinib and key metabolites AZ5104 and AZ7550. Osimertinib was designed to covalently bind to epidermal growth factor receptors, allowing it to achieve nanomolar cellular potency . Covalent binding was observed in incubations of radiolabeled osimertinib with human and rat hepatocytes, human and rat plasma, and human serum albumin. Osimertinib, AZ5104, and AZ7550 were predominantly metabolized by CYP3A. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 23 publications
7
104
1
Order By: Relevance
“…Indeed, recombinant CYP2A6 did not produce this metabolite (Figure 2A). It should be noted however that Dickinson et al observed some activity of recombinant CYP2A6 with osimertinib (26). Formation of DM-2 in the HLM panel agreed less well with the recombinant protein data, as correlation with CYP3A4 activity was considerably weaker than with CYP2A6, CYP2B6 and CYP2C8.…”
Section: In Vitro Metabolism Of Osimertinib: Similarities and Differementioning
confidence: 64%
See 1 more Smart Citation
“…Indeed, recombinant CYP2A6 did not produce this metabolite (Figure 2A). It should be noted however that Dickinson et al observed some activity of recombinant CYP2A6 with osimertinib (26). Formation of DM-2 in the HLM panel agreed less well with the recombinant protein data, as correlation with CYP3A4 activity was considerably weaker than with CYP2A6, CYP2B6 and CYP2C8.…”
Section: In Vitro Metabolism Of Osimertinib: Similarities and Differementioning
confidence: 64%
“…In humans, CYP3A enzymes have been reported to be primarily responsible for both the generation and the further metabolism of the key active metabolites, DM-1 (AZ5104) and DM-2 (AZ7550) (25,26,31). In the humanized model exposure to DM-1 decreased to a similar extent in both mouse lines after RIF pre-treatment (Figure 4C,D).…”
Section: Osimertinib Disposition Following the Induction Of Cyp3a4 Inmentioning
confidence: 99%
“…21,23 A single oral dose of osimertinib was slowly absorbed, and after C max , concentrations declined in a monophasic manner. The oral absolute bioavailability of an 80mg single oral dose of osimertinib in healthy subjects was 69.8%, suggesting that osimertinib is well absorbed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Two active metabolites, AZ5104 and AZ7550, 22 circulate at approximately 10% of osimertinib exposure at steady state. 23 Of the excreted radioactivity, unchanged osimertinib constitutes approximately 1.2% in feces and 0.71% in urine (in samples up to 7 days postdose) indicating that the majority of the elimination occurs via metabolism. 23 Of the excreted radioactivity, unchanged osimertinib constitutes approximately 1.2% in feces and 0.71% in urine (in samples up to 7 days postdose) indicating that the majority of the elimination occurs via metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation